Woodchuck hepatitis virus replication and antigen expression gradually decrease in preneoplastic hepatocellular lineages - Li, Yanhua; Kopp-Schneider, Annette; Protzer-Knolle, Ulrike; Bannasch, Peter (Journal of hepatology, 2002)
Background/Aims: Hepatocellular carcinomas elicited in woodchucks by the woodchuck hepatitis virus (WHV) emerge gradually from parenchymal areas of minimal structural deviation via two predominant preneoplastic hepatocellular lineages, composed of either glycogenotic/basophilic or amphophilic/basophilic cell foci. In this study we analyzed WHV replication during neoplastic development in both lineages. Methods: In minimal deviation areas, preneoplastic hepatocellular foci, and hepatocellular neoplasms, developing in 16 WHV-carriers 31-38 months after WHV-inoculation, the proportion of hepatocytes containing WHV replicative intermediates (as detected by in situ hybridization for WHV DNA) and immunoreactive for WHV core and surface antigens was assessed. Results: Appearance of WHV replicative intermediates and expression of antigens were limited to the cytoplasm of hepatocytes and were strongly correlated (P<0.0001), both showing high levels in minimal deviation areas, but markedly reduced amounts in all types of preneoplastic hepatic focus (P<0.0001), and in hepatocellular adenomas. Most hepatocellular carcinomas were negative for WHV replicative intermediates and antigens. Conclusions: In both the glycogenotic-basophilic and the amphophilic-basophilic preneoplastic hepatocellular lineage, WHV replication and antigen expression gradually decrease early during the preneoplastic phase. The close correlation of these changes with metabolic aberrations characterizing preneoplastic hepatocellular lineages suggests that oncogenic effects mimicking insulin/glucagon imbalances may be responsible for the repression of hepadnaviral replication.